2015
DOI: 10.1007/s11356-015-5811-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maritime traffic on polycyclic aromatic hydrocarbons, metals and particulate matter in Venice air

Abstract: Harbours are important hubs for economic growth in both tourism and commercial activities. They are also an environmental burden being a source of atmospheric pollution often localized near cities and industrial complexes. The aim of this study is to quantify the relative contribution of maritime traffic and harbour activities to atmospheric pollutant concentration in the Venice lagoon. The impact of ship traffic was quantified on various pollutants that are not directly included in the current European legisl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 17 publications
5
35
0
3
Order By: Relevance
“…The sources' identification and sources' impact evaluation have been carried out by the use of the atmospheric vanadium concentration, to calculate the primary contribution of ship traffic to PM 10 , the Positive Matrix Factorization (PMF), and the Diagnostic Ratios (DR). Moreover, by integrating our data with those obtained in other previous studies (Contini et al, 2012;Gregoris et al, 2016), this study provides a significant temporal trend of the characterization of aerosol in the Venice Lagoon in terms of PM 10 concentration and its elemental characterization.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The sources' identification and sources' impact evaluation have been carried out by the use of the atmospheric vanadium concentration, to calculate the primary contribution of ship traffic to PM 10 , the Positive Matrix Factorization (PMF), and the Diagnostic Ratios (DR). Moreover, by integrating our data with those obtained in other previous studies (Contini et al, 2012;Gregoris et al, 2016), this study provides a significant temporal trend of the characterization of aerosol in the Venice Lagoon in terms of PM 10 concentration and its elemental characterization.…”
Section: Introductionsupporting
confidence: 56%
“…The constant R has a suggested value of 8205.8 (Agrawal et al, 2009); V a is the ambient vanadium concentration; F V,HFO is a term indicating the typical V content (ppm) in heavy fuel oils (HFO) used by vessels. In this work the value of 65 ± 25 ppm was used, as previously done in the harbors of Venice (Gregoris et al, 2016), and Brindisi (Cesari et al, 2014). The values of the primary contribution of ship traffic to PM 10 in MM and PS were published in Gregoris et al (2016) as averages of the period 2007-2013.…”
Section: Primary Contribution Of Ship Traffic To Pm 10mentioning
confidence: 99%
See 1 more Smart Citation
“…The European Directive 2005/33/EC [7] introduced more stringent marine-fuel sulphur limits for ships at berth or cruising inside European coastal waters. This reduced the contribution of ship cruising, manoeuvring and hoteling to atmospheric pollutants such as SO 2 [8] and primary particulate matter (PM 10 , and PM 2.5 ) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ships may access the lagoon only through two inlets and may sail only through narrow canals that are dredged within the shallow water. The movement of ships in the lagoon is an important issue for the city of Venice, since it has been shown that it has an impact on the city in terms of both air pollution (Gregoris et al, 2016) and wave generation (Parnell et al, 2015). Indeed, the passage of large cruise ships has given rise to a progressive regulation (Casagrande, 2015).…”
Section: Introductionmentioning
confidence: 99%